Strategy on Developing English Learning Material for Specific Purposes - Heryan Ardhi Kusuma; Sigit Apriyanto (Universitas Muhammadiyah Mataram, 2018)
Teaching material is an important tool to achieve learning goals. Teaching materials can help teachers prepare learning activities, and guide students in learning, both at school and at home. Therefore, teaching materials must be prepared based on the basic principles and steps of the systematic development of teaching materials as well as the assessment criteria to use in the field to ensure the quality of teaching materials developed. This paper discusses developing learning material for ESP (English for Specific Purposes). The method used to describe the development of learning material is by conducting a qualitative in which the writer did the document review of some related articles and books. The discussion area about the definition, the principles, the procedures, and the practical undertaking of developing learning material for ESP. The development of teaching materials for creative and integrated English learning is an effort to facilitate student learning, moving from the old paradigm to the new paradigm. Hopefully, the main target of learning for them is not only the result of learning in the form of numbers, but the courage to show the ability through real action under the skills and knowledge mastered.